The association between vitamin D and BDNF on cognition in older adults in Southern Brazil - Quialheiro, Anna; d´Orsi, Eleonora; Moreira, Júlia Dubois; Xavier, André Junqueira; Peres, Marco Aurélio (Revista de Saúde Pública, 2022)
OBJECTIVE: To estimate the association between vitamin D and the cognitive decline of older adults and evaluate whether this association is mediated by brain-derived neurotrophic factor (BDNF) serum concentration. METHODS: Cross-sectional study nested in a population-based cohort. Of the 604 participants in the complementary examination of the EpiFloripa Study, 576 older adults (60 years or older) were eligible for the study. The outcome is cognitive decline evaluated by the Mini-Mental State Examination, the exposure is vitamin D, and BDNF is the mediator. The control variables are age, sex, per capita family income, and educational level. The direct effect of vitamin D and BDNF on cognitive decline and the indirect effect mediated by BDNF was evaluated using path analysis, with the estimation of standardized coefficients. RESULTS: Among the participants, we observed a direct and positive effect of vitamin D on cognitive function (Coef: 0.06; 95%CI 0.02 to 0.11; p < 0.001) and serum BDNF concentration (Coef: 21.55; 95%CI 9.92 to 33.17; p = 0.002), i.e., the higher the vitamin D, the higher the cognitive function and serum level of BDNF. CONCLUSION: There was an association between vitamin D on serum BDNF and on cognitive decline in older adults. Moreover, BDNF did not have an effect on cognitive decline, so BDNF was not a mediator of the vitamin D effect on cognitive decline.